1996
DOI: 10.1002/(sici)1097-0142(19960801)78:3<627::aid-cncr43>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A rationale for expanding the endpoints for clinical trials in advanced pancreatic carcinoma

Abstract: BACKGROUND. Using classical endpoints, such as response rate and survival, as the sole measures of benefit, little progress has been made in the treatment of advanced pancreatic carcinoma in the past 30 years. We challenge the assumption that response rate and survival are the only appropriate endpoints for clinical trials in this disease setting. METHOD.A review of the literature and roundtable discussion were undertaken. RESULTS. Using current imaging techniques, it is inherently difficult to distinguish pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 45 publications
0
13
1
2
Order By: Relevance
“…Furthermore, Diehl and colleagues described a 99.9% decrease in ctDNA levels during treatment of colorectal patients, whereas the tumor volume (composed of live and dead neoplastic cells in addition to stromal cells) decreased only slightly (Diehl et al., 2008). In pancreatic cancer patients, measurement of treatment efficacy by imaging is particularly challenging, as the tumor is often surrounded by a dense fibrotic tissue, making radiological (CT and PET scan) detection difficult (Rothenberg et al., 1996; Duffy et al., 2010). Thus, therapy decisions in this patient group are based not only on imaging, but also on evaluation of the CA19‐9 level, which is currently the most common and extensively used blood biomarker in pancreatic cancer management despite having several limitations (Duffy et al., 2010; Ballehaninna and Chamberlain, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Diehl and colleagues described a 99.9% decrease in ctDNA levels during treatment of colorectal patients, whereas the tumor volume (composed of live and dead neoplastic cells in addition to stromal cells) decreased only slightly (Diehl et al., 2008). In pancreatic cancer patients, measurement of treatment efficacy by imaging is particularly challenging, as the tumor is often surrounded by a dense fibrotic tissue, making radiological (CT and PET scan) detection difficult (Rothenberg et al., 1996; Duffy et al., 2010). Thus, therapy decisions in this patient group are based not only on imaging, but also on evaluation of the CA19‐9 level, which is currently the most common and extensively used blood biomarker in pancreatic cancer management despite having several limitations (Duffy et al., 2010; Ballehaninna and Chamberlain, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, single‐agent 5‐fluorouracil (5‐FU) has been a frequently used treatment that has produced tumor response rates in the range of 0–19% (since 1985 when computed tomography [CT] assessment of tumor response became standard) and a median survival of 4.2–5.5 months 1. A review of the literature on investigational new drugs (28 Phase II trials involving 25 agents) showed that, to date, there has been no improvement in patient outcome, with a median objective response rate of 0% (range, 0–14%) and a median survival of 3 months (range, 2–8.3 months) 2…”
mentioning
confidence: 99%
“…This observation led to the use of the clinical benefit response (CBR) as an alternative outcome measurement to evaluate the efficacy of gemcitabine in pancreatic cancer. CBR is a measure of clinical improvement in terms of pain intensity, analgesic consumption, performance status, and weight change 33,34. A patient will be considered a responder if rated “positive” for either of the primary measures of pain or performance status without a negative rating in the other parameters.…”
Section: Single‐arm Studiesmentioning
confidence: 99%